Effect of the drying process of sainfoin on in vitro fermentation parameters - Joy M.; Rufino-Moya P.J.; Blanco M.; Lobón S. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Sainfoin (Onobrychis viciifolia) is an interesting legume due to its high production and its content of condensed tannins, which reduce methane production in the rumen. It is advisable to preserve this forage to optimize its use for animal feeding because two thirds of the annual production are obtained in the first spring cut. The objective of the present study was to evaluate the effects of different drying processes on the chemical composition and the in vitro fermentation parameters. Sainfoin was collected at the early flowering stage and was dried under the following conditions: freeze-dried, sun-dried and dried at 40, 60 and 80 ºC in an airforced oven. After 24 h of incubation, contents of ammonia and volatile fatty acids were determined and in vitro organic matter degradability (IVOMD) was estimated. Freeze-dried sainfoin presented the lowest content of crude protein and fibres (neutral and acid detergent fibres) and the greatest condensed tannins (CT) content (P<0.05). In contrast, the 80ºC-oven dried sainfoin presented the highest fibre contents and the lowest CT content. Regarding the in vitro fermentation, the drying method had not effect on most of the assessed parameters, except for IVOMD (P<0.001), showing the lowest value the sun-dried sainfoin. In conclusion, the different drying conditions affected the chemical composition, but they had minor effect on the in vitro fermentation.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)